1986
DOI: 10.1128/jb.168.3.1142-1146.1986
|View full text |Cite
|
Sign up to set email alerts
|

Photophosphorylation and oxidative phosphorylation in intact cells and chromatophores of an aerobic photosynthetic bacterium, Erythrobacter sp. strain OCh114

Abstract: Light-induced ATP synthesis was studied in intact cells and chromatophores of Erythrobacter sp. strain OChll4. ATP synthesis was measured by both the pH method and the luciferin-luciferase luminescence method. The rate of ATP synthesis was moderate (a typical value of 0.65 mol of ATP per mol of bacteriochlorophyll per min), and synthesis was inhibited by antimycin A. ATP was synthesized under illumination only under aerobic conditions and not under anaerobic conditions. This characteristic was similar to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…The importance of light controlling AAP bacterial activity has been shown by several pure culture studies (Shiba, 1984;Okamura et al, 1986;Holert et al, 2011;Tomasch et al, 2011;Hauruseu and Koblížek, 2012). However, we did not see a significant effect of light in short term incubations.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The importance of light controlling AAP bacterial activity has been shown by several pure culture studies (Shiba, 1984;Okamura et al, 1986;Holert et al, 2011;Tomasch et al, 2011;Hauruseu and Koblížek, 2012). However, we did not see a significant effect of light in short term incubations.…”
Section: Discussioncontrasting
confidence: 56%
“…This presumed advantage led to the hypothesis that one type of photoheterotroph, aerobic anoxygenic phototrophic (AAP) bacteria, would be most abundant in oligotrophic systems (Kolber et al, 2000), but subsequent work demonstrated that AAP bacteria are abundant in eutrophic estuaries and coastal waters when compared with the open oceans Jiao et al, 2007;Lami et al, 2007;Waidner and Kirchman, 2007;Ritchie and Johnson, 2012). Light has been shown to positively affect the growth rate and other aspects of AAP bacterial activity in laboratory experiments (Shiba, 1984;Okamura et al, 1986;Holert et al, 2011;Tomasch et al, 2011;Hauruseu and Koblížek, 2012), but it has complex effects on natural microbial communities which include photoheterotrophic microbes Straza and Kirchman, 2011;Ruiz-González et al, 2012a;Ruiz-González et al, 2012b). Data on growth-related activity in natural communities would help elucidate the advantages of photoheterotrophy and whether photoheterotrophic microbes change models of carbon cycling (Karl, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The photosynthetic competence of the AAPs has been demonstrated by spectroscopic analyses (9,27,32) and infrared (IR) kinetic fluorescence measurements (16,21). It was shown that light exposure of AAP cells inhibits respiration (10,16) and increases their cellular ATP concentration (2,25). This indicates that AAPs are able to partially replace oxidative phosphorylation with photophosphorylation.…”
mentioning
confidence: 99%
“…This type of photochemistry is present not only in all purple photosynthetic bacteria and Chloroflexus species but also in the aerobic, BChl-containing bacteria (27,61). However, the primary photochemistry in the RC of R. denitrificans and the light-induced pH change of the suspension disappear under anoxic conditions (27,44,45). Light stimulates growth for a short period under anoxic conditions in the presence of high concentrations of trimethylamine N-oxide or nitrate as an external electron acceptor when the cells have been precultivated aerobically in the dark (24)(25)(26).…”
mentioning
confidence: 99%